STRATEGI PEMASARAN DIGITAL UNTUK MENDORONG ADOPSI SISTEM MANAJEMEN INSPEKSI RIG TERINTEGRASI (IRIMS™) DALAM INDUSTRI PENGEBORAN MINYAK DAN GAS - setiadi; Eko Nugroho; Christian Lian; Yulitha Widha Pratama (JOISCOM (Journal of Islamic Communication), 2026)
The oil and gas industry heavily relies on drilling rig integrity managed through periodic inspections. However, traditional and fragmented inspection data management—scattered across PDFs, spreadsheets, and manual records—creates chronic problems such as poor asset condition visibility, expiring certifications, delayed non-conformance report (NCR) follow-ups, and inefficient audit processes. This situation increases operational and safety risks. This study analyzes effective digital marketing strategies to accelerate the adoption of the Integrated Rig Inspection Management System (IRIMS™), a cloud-based integrated platform that unifies inspection scheduling, certification tracking, and NCR monitoring. Using a quantitative survey-based approach with drilling industry practitioners, this research employs the Technology Acceptance Model (TAM) and Diffusion of Innovation Theory to build a structural model (SEM) examining relationships between digital marketing strategies, technology perception, and adoption. The analysis results indicate that the most significant digital marketing strategies influencing adoption are in-depth educational approaches and intensive communication through professional channels. Technical webinars, LinkedIn thought leadership, and pilot project demonstrations proved most effective in shaping positive perceptions of system usefulness and building user trust. These findings confirm that education-focused digital marketing can overcome adoption barriers such as cultural resistance and data security concerns, thereby accelerating digital transformation in rig inspection management. IRIMS™ implementation has the potential to significantly improve data transparency, process optimization, and audit readiness.